Development and validation of sexual-and-gender minority malay women care module according to Islamic values for service providers in Malaysia - Jaapar, Sharifah Zubaidiah Syed (2024)
Sexual and gender minority among Malay women (SeGMen) is increasing, with high risk of developing mental health illness. However, service providers in Malaysia lack the skills and guidelines to provide services to SeGMen. Thus, this study aims to develop and validate a SeGMen care module according to Islamic values for service providers in Malaysia by understanding the construction, psychosocial and spiritual distress, and help-seeking behaviour of SeGMen from the perspectives of SeGMen and service providers. This study involved three phases. Phase 1 is the need analysis, Phase 2 is the design and development, and Phase 3 is the evaluation of the usability of the module. In Phase 1, a scoping review of 22 studies related to SeGMen was done to explore the necessity of developing the module. Phase 2 is designing and developing the module. Designing the module was done by interviewing 30 SeGMen and 20 service providers. Later, the development of the module involved 5 experts in a modified nominal group technique (NGT). In Phase 3, the usability of the module was evaluated via content validity by 5 experts, and reliability was tested with 30 service providers. Results of Phase 1 revealed three themes: construction of same-sex attraction (SSA), experience as minority and unmet service needs. From the need analysis, there is a need to develop a SeGMen care module to train the service providers dealing with SeGMen. In Phase 2 designing module, the interviews from SeGMen revealed four themes: early life crisis as a precursor for identity construction, minority identity conflict, manoeuvring self as a resilient SeGMen and self reformation. From service providers’ views, three themes were emerged: navigating through crises, challenges in handling crises and spirituality needs. From the available data, a module was designed to include 17 elements with 5 topics. In developing the module, 5 experts in the modified NGT reached a consensus and accepted all 17 elements and suggested 6 topics of the training module. Finally, in Phase 3, the module showed good content validity (more than 70% agreement) and reliability (α > 0.95). As a conclusion, a SeGMen care module according to Islamic values is usable to train service providers dealing with SeGMen.